2018
DOI: 10.1038/s41467-018-04829-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous buckling of contractile poroelastic actomyosin sheets

Abstract: Shape transitions in developing organisms can be driven by active stresses, notably, active contractility generated by myosin motors. The mechanisms generating tissue folding are typically studied in epithelia. There, the interaction between cells is also coupled to an elastic substrate, presenting a major difficulty for studying contraction induced folding. Here we study the contraction and buckling of active, initially homogeneous, thin elastic actomyosin networks isolated from bounding surfaces. The network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 43 publications
(56 reference statements)
4
52
0
Order By: Relevance
“…Thus, it is even more remarkable that we observe a similar qualitative and quantitative behavior of the actomyosin contraction. The timescale of the contraction agrees well with the bead velocity we determined in Figure 1g and previous works on actomyosin contraction: [27,29,[30][31][32][33][34][35][36][37]46] Within 6 min, we expect a displacement of approximately 36 µm, which is comparable to the droplet radius. The filaments condense to a small fraction of the droplet's volume (see Figures S10 and S11, and Video S4, Supporting Information).…”
Section: Actomyosin Contraction In Microfluidic Dropletssupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, it is even more remarkable that we observe a similar qualitative and quantitative behavior of the actomyosin contraction. The timescale of the contraction agrees well with the bead velocity we determined in Figure 1g and previous works on actomyosin contraction: [27,29,[30][31][32][33][34][35][36][37]46] Within 6 min, we expect a displacement of approximately 36 µm, which is comparable to the droplet radius. The filaments condense to a small fraction of the droplet's volume (see Figures S10 and S11, and Video S4, Supporting Information).…”
Section: Actomyosin Contraction In Microfluidic Dropletssupporting
confidence: 90%
“…This is in excellent agreement with previous studies, in which a global contraction was observed for a myosin motor to actin ratio of R M = 0.01. [30,45,46] This is comparable to our experiments with R M = 0.013, for which we observe global contraction and aster formation. Doubling the actin content (i.e., reducing the HMM to actin ratio by half) leads to a stalled contraction as also observed with reconstituted myosin filaments, consistent with a previous study.…”
Section: Actomyosin Contraction In Microfluidic Dropletssupporting
confidence: 89%
“… 33 It was not observed in the other 3D studies as those systems were investigated at constant ATP concentration at reaction-limited regime. 29 , 30 These observations suggest that the active stress is determined by the stall force of kinesin motors, which is independent of the ATP concentration, and by the cross-linking nature of the motors. To test the importance of the motor concentration, we decreased the kinesin concentration by 10-fold (to 1.7 nM) and indeed did not observe the instability ( Figure 4 E).…”
Section: Resultsmentioning
confidence: 94%
“…Remarkably, the actomyosin cortex in Caenorhabditis elegans embryos generates chiral torques, which generates counterrotating cortical flows that are used to establish the left-right symmetry of the developing organism (Naganathan et al, 2014). Finally, let us note that the contractility of thin active gel layers, be it the actin cortex or a cell monolayer, can generate instabilities that lead to three dimensional shape changes (Hannezo et al, 2011;Ideses et al, 2018;Shyer et al, 2017).…”
Section: Hydrodynamics Of Motor-filament Networkmentioning
confidence: 99%